The Gut Microbiomes of Wild Rodents within Forested Environments in Sarawak, Borneo - Muhammad Amin Iman, Azmi; Julius Willian, Dee; Muhd Amsyari, Morni; NUR AFIQAH AQILAH, AZHAR; Nor Al-Shuhadah, Sabarudin; Emy Ritta, Jinggong; Syamzuraini, Zolkapley; Cheng Siang, Tan; Faisal Ali, Anwarali Khan (UNIMAS Publisher, 2024)
The gut microbiota of rodents is shaped by highly diverse bacterial communities. Within the gut environment, there are core gut bacteria that are responsible for facilitating essential bodily processes while maintaining the health of the host rodents. Currently, research on the gut microbiota of wild rodents in Borneo remains limited, especially those encompassing the potential influence of environmental factors. Through the Next-Generation Sequencing (NGS) performed using Oxford Nanopore Technologies, a total of 1052 bacterial genera were detected from 16 rodent individuals of six rodent species. These bacteria were found to be prevalent in the gut microbiota of wild rodents in forested regions. Several bacterial families of importance belonging to the phylum Bacillota were identified, including Lachnospiraceae (18%), Lactobacillaceae (20%) and Oscillospiraceae (19%). They were found to have a high relative abundance when compared with other bacterial families. The diversity of gut microbes among individual rodents showed no significant differences. However, the gut microbiome composition of wild rodents appears to have been influenced by the host species and their life stages. The outcome of this study allows for a better understanding of the prevailing core microbiome members shared across multiple wild rodent individuals within forested areas.